A numerical study on effects of friction-induced thermal load for rail under varied wheel slip conditions. (April 2019) - Srivastava, Jay Prakash; Sarkar, Prabir Kumar; Kiran, MV Ravi; Ranjan, Vinayak
A finite element-based simulation was carried out to investigate the effects of friction-induced thermal load on rail under varied wheel slip conditions. The surface temperature rise from six different percentage slips (1%, 1.5%, 2%, 5%, 8.5%, and 10%) at the contact interface was examined for eight-wheel pass. The residual stresses and accumulated plastic strains evolved by the effect of localized temperature rise are estimated. Analytical formulation for conduction mode of heat transfer at the contact patch is used to estimate the temperature distribution. The interaction of thermal-elastic-plastic field conditions is obtained by a proposed simulation model. This is implemented in commercial finite element software ANSYS 14.0. In order to capture the steep thermal gradient beneath the contact surface, refined mesh is used in the upper layers up to a depth of 2 mm of the simulation domain. For better manifestation of thermally affected material layers, a temperature dependent bilinear-kinematic hardening material condition is applied. Results indicate the maximum temperature rise at about 0.6 a from the trailing end in the contact ellipse of semi-major axis a . At higher slippage conditions the initial pearlitic rail steel gets converted to martensite which is often observed on rail surface as white etching layer known to be associated with rolling contact fatigue. The study reveals the mechanisms of thermally induced defects observable on rail surface. The outcomes, in addition, can provide useful information for the development of thermo-mechanically superior rail steels.